A state-of-the-art review on alumina toughened zirconia ceramic composites - Abbas M.K.G.; Ramesh S.; Tasfy S.F.H.; Lee K.Y.S. (Elsevier Ltd, 2024)
Alumina-zirconia composites (ATZs) are a class of advanced ceramics that have attracted significant attention due to their excellent mechanical properties. These properties make ATZs suitable for a wide range of applications. This review provides a comprehensive overview of the current state of understanding of ATZs. The review begins with a brief introduction to the properties of zirconia and alumina ceramics. The different methods for combining zirconia and alumina ceramics are then discussed. The effects of sintering conditions on the tetragonal phase stability, densification, mechanical properties, evolution of microstructural and grain size of the alumina toughened zirconia are also presented. Previous studies have reached a consensus on the influence of sintering temperature, sintering time, and alumina content on the properties of ATZ composites. Generally, elevating sintering temperatures and prolonging sintering times result in heightened densities and improved mechanical properties. However, the impact of alumina content is less straightforward, as divergent findings exist, some studies indicate that higher alumina contents correspond to diminished properties, while others reveal no significant effect. Additionally, the sintering method emerges as a pivotal determinant impacting the properties of ATZ ceramics. Notably, microwave sintering has demonstrated superiority over traditional methods, yielding heightened properties. Optimal density and mechanical properties of ATZ composites can be achieved through meticulous control of sintering conditions. By comprehending the factors influencing ATZ, the production of ATZ composites tailored to specific applications becomes attainable, offering the prospect of desired properties. 2023 The Authors